Validation of psychomotor tasks by Simbionix LAP Mentor simulator and identifying the target group. Issue 5 (3rd September 2017) - Elessawy, Mohamed; Wewer, Arne; Guenther, Veronika; Heilmann, Thorsten; Eckmann-Scholz, Christel; Schem, Christian; Maass, Nicolai; Noe, Karl-Günter; Mettler, Liselotte; Alkatout, Ibrahim
Abstract: Background: This study addresses target group reliability and task validity for training on a laparoscopic simulator. Material and methods: Data were collected on 64 participants prospectively at the Department of OB/GYN, University Hospitals Schleswig-Holstein, Campus Kiel. The Simbionix LAP Mentor for laparoscopic simulation was used to test trainees. Each participant received a questionnaire to clarify his/her medical position, surgical experience, and previous virtual reality (VR) experience, including video gaming experience. Pre- and post-tests were performed. Performances were analyzed for task completion and total time. Results: All participants revealed a significant improvement in the post-test compared with the pre-test ( p < .005), independent of their previous level of experience. Regarding accomplishment of the assigned task, the experts revealed in the pre-test an advantage in tasks 1–4 and 6–8. The beginners revealed wide-ranging improvements in tasks 3, 5, 8, and 9 between the pre-test and the post-test compared with novices in laparoscopic surgery (residents), and a wide range of improvements relative to experts. VR experience and video gaming exposure revealed an advantage in the pre-test; however, participants without previous exposure were able to narrow the gap, revealing extensive improvements in the post-test. Conclusion: The trainer could be beneficial for medical students and surgical novices.